PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR IPA - Ardiawan, I Ketut Ngurah; Yadnya Diari, Komang Puteri (Adi Widya: Jurnal Pendidikan Dasar, 2020)
This study aims to determine the increase in activeness and learning achievement of science students in fifth grade elementary school after applying contextual learning models. This research is Classroom Action Research. The subjects of this study were 24 students of Class V of SDN 1 Agung Package. The object of this research is the activeness and learning achievement of science. Activity data was collected using a questionnaire and data on learning achievement were collected by tests. Activity data and learning achievement were analyzed by quantitative descriptive analysis methods. The analysis showed that the average activity in the first cycle of 40% had increased in Cycle II to 83%. The average student learning achievement in the first cycle to an average class (M) of 66, absorbency (DS) of 66% and mastery learning (KB) of 69% have increased in Cycle II with an average class (M) by 80, absorption (DS) by 80% and mastery learning (KB) by 100%. Based on the results of the study it can be concluded that the application of contextual learning learning models can increase the activeness and achievement of science learning in fifth grade elementary school students No. 1 Agung Package, Buleleng District, Buleleng Regency.